Modelo de difusão e adoção de inovações: um estudo na área farmacêutica - Springer, Rodrigo Eduardo (Universidade do Vale do Rio do Sinos, 2008)
Diffusion of an innovation can play a central role in the generation of competitive advantage. This research aimed to analyze the process of innovation diffusion in the pharmaceutical sector, by identifying the factors which influence the adoption of a new medicine. An antidepressive product (venlafaxine chloridrate) was the object of the study. A survey was performed with a sample of 108 general clinic physicians who work in cities of Vale do Sinos and of the mountain area of Rio Grande do Sul State, Brazil. The results of the analyses indicate that physicians who give more importance to the existence of proved satisfactory clinical results where the ones who adopted the product to a lower extend. Besides, the results show that physicians who give more importance to positive aspects of the active principle where the ones who adopted the product more. Finally, the results showed that physicians who give more value to the propaganda of laboratories and who attend medical congresses tend to be more innovative.
Keywords: adoção; medicamentos inovadores; difusão; adoption; innovative medicines; diffusion; Ciências Sociais Aplicadas